Internalisasi Semangat 2D2K Sekami dalam Membangun Karakter Misioner Anak di Stasi Hati Amat Kudus Tuhan Yesus Lewoloba - Maria Fatima Bunda Nuhan; Hendrikus Febrianto Fernandez; Krisantus Minggu Kwen (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to analyze the internalization of the 2D2K spirit (Prayer, Charity, Sacrifice, and Witness) in fostering the missionary character of children at Stasi Hati Amat Kudus Tuhan Yesus Lewoloba. The study was motivated by the limited internalization of 2D2K values among Holy Childhood Association (SEKAMI) members despite their active participation in faith formation activities. A descriptive qualitative approach was employed, involving SEKAMI facilitators, children, parents, and the Outstation Head as research participants. Data were collected through interviews, observations, and documentation and analyzed descriptively. The findings indicate that the internalization of the 2D2K spirit takes place through four interconnected processes: socialization, externalization, combination, and internalization. Prayer strengthens children’s relationship with God and nurtures their spiritual life, while charity and sacrifice develop social concern, solidarity, generosity, and a willingness to serve others. Witness encourages children to express and live out their faith in everyday life. These findings imply that the internalization of the 2D2K spirit plays a significant role in developing faithful, caring, responsible, and missionary-minded children who are prepared to witness to Christ in their families, schools, communities, and the Church.